2015
DOI: 10.5673/sip.53.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Trgovački centri i promjene u gradskoj jezgri: slučaj Zadra

Abstract: SAŽETAK Trgovački centri specifičan su proizvod i simbol potrošačkog društva i kulture, a njihova je pojava bila jedan od najvidljivijih znakova transformacije postsocijalističkih gradova. Namjera ovog rada ukazati je na povezanost procesa decentralizacije i suburbanizacije trgovine s promjenama u zadarskoj gradskoj jezgri. Prvi cilj istraživanja bio je utvrditi stanje zadarske povijesne jezgre s obzirom na njezine komercijalne, poslovne i turističke funkcije. Kako bi se ustanovila zastupljenost pojedinih tipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Attention has already been drawn to the problem of the lack of coherent strategy and vision for city development in Zagreb, which leads to the non-systematic treatment of urban spaces (Svirčić Gotovac, 2010). Importance of strategic plans defining overall objectives of city centre revitalisation (Tonković, 2015) and of strategic interventions in the scope of comprehensive urban regeneration is highlighted for post-socialist cities in general (Keresztély & Scott, 2012). A higher level of participation in the urban regeneration processes is also called for (Compare with Svirčić Gotovac & Kerbler, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Attention has already been drawn to the problem of the lack of coherent strategy and vision for city development in Zagreb, which leads to the non-systematic treatment of urban spaces (Svirčić Gotovac, 2010). Importance of strategic plans defining overall objectives of city centre revitalisation (Tonković, 2015) and of strategic interventions in the scope of comprehensive urban regeneration is highlighted for post-socialist cities in general (Keresztély & Scott, 2012). A higher level of participation in the urban regeneration processes is also called for (Compare with Svirčić Gotovac & Kerbler, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In this light, we should mention processes of depopulation and increases in the share of older population and single-member households that increasingly characterise historical city cores along the Croatian Littoral, along with losing the role of the main retail centres for their cities, while gaining a new characteristic: that of tourist centres (Poljičak, 2014). Research has shown a link between the decentralisation of retail, declining visits to the city core, and an impression of "emptiness" in the city centre outside of the peak tourist season (Tonković, 2015).…”
Section: The Causes Of Abandonment Of Commercial Premisesmentioning
confidence: 99%
See 2 more Smart Citations